Association between left ventricular reverse remodelling and the B-type natriuretic peptide–cGMP cascade after anterior acute myocardial infarction - Satoshi Yasuda; Kunihiro Nishimura; Kensuke Takagi; Hiroyuki Takahama; Naoto Minamino; Masashi Fujino; Satoshi Honda; Yasuhide Asaumi; Yu Kataoka; Fumiyuki Otsuka; Soshiro Ogata; Teruo Noguchi; et al. (Open Heart)
Background The role of cyclic guanosine 3′,5′-monophosphate (cGMP) after acute myocardial infarction (AMI) is not well understood despite its significance as a second messenger of natriuretic peptides (NPs) in cardiovascular disease. We investigated the association between the NP-cGMP cascade and left ventricular reverse remodelling (LVRR) in anterior AMI.Methods 67 patients with their first anterior AMI (median age, 64 years; male, 76%) underwent prospective evaluation of plasma concentrations of the molecular forms of A-type and B-type natriuretic peptide (BNP) and cGMP from immediately after primary percutaneous coronary intervention (PPCI) to 10 months post-AMI. The estimated mature BNP (emBNP) concentration was calculated as the difference between total BNP and prohormone of BNP (proBNP) concentrations. Patients were divided into LVRR and non-LVRR groups on the basis of residuals between observed change in left ventricular end-systolic volume index on MR during the first 11 months after AMI and change adjusted for proBNP concentration immediately post-PPCI, which was calculated with regression. The LVRR group (n=33) had residuals below the median; the non-LVRR group (n=34) had residuals at or above the median.Results The LVRR group had higher freedom from major adverse cardiac and cerebrovascular events (MACCEs) than the non-LVRR group during a median follow-up of 9.9 years (p=0.008). The presence of LVRR (HR 0.256; 95% CI 0.081 to 0.809; p=0.028) and peak creatine phosphokinase–myocardial band level (per 100 IU/L) (HR 1.22; 95% CI 1.02 to 1.46; p=0.027) were independent predictors of MACCE after adjusting for age, male sex, infarct size and hypertension. Multivariable analyses identified logarithmic proBNP and emBNP concentrations from 12 hours to 5 days post-AMI and logarithmic cGMP concentration from immediately post-PPCI to 3 days post-AMI as independent predictors of LVRR (p<0.05).Conclusions Early-phase BNP-cGMP cascade activation might play a crucial role in LVRR in anterior AMI.